Songs to Seven Strings Russian Guitar Poetry and Soviet "Mass Song" - Smith, Gerald Stanton (Indiana University Press, 1984)
In the early 1960s, searching for a fresh style and a new way of bringing their words to the Soviet public, a number of Russian poets began singing their verse to their own solo accompaniment on the traditional seven-stringed guitar. At about the same time, tape recorders became widely available in the USSR. Privately recorded and circulated on tape-a process called magnitizdat-guitar poetry quickly became the most popular form of dissident culture in the post-Stalin period. The guitar poets and their songs are known and loved throughout the USSR. Songs to Seven Strings is the first book in any language about this unusual literary genre. Smith places guitar poetry within the context of official "mass song"; "middle ground" songs, where official and unofficial cultures overlap; and the strong underground traditions of the gypsy song, cruel romance, and criminal song.